Au-rich bimodal-mafic type volcanogenic massive sulphide deposit associated with Jurassic arc volcanism from the Central Pontide (Kastamonu, Turkey) - Gunay, Kurtulus; Oyan, Vural; Donmez, Cahit; Cavdar, Bugra; Ciftci, Emin; Chugaev, Andrey V.; Ma, Chang-Qian (Elsevier, 2022)
The central part of the Pontide Orogenic Belt, located in northern Anatolia, is a segment of the Alpine-Himalayan orogeny. Cangaldag Metamorphic Complex (CMC) occurs within this segment which consists of ensimatic island arc volcanics and deep sea sediments which occasionally cut cross by mafic sills/dykes. They were exposed to metamorphism under the greenschist facies conditions and remain in tectonic contact with each other. The Say yayla mineralization is one of the recently discovered volcanogenic massive sulfide (VMS) deposits in the CMC with a remarkable Au content. The mafic and felsic metavolcanic rocks are the host-rocks of the Say Yayla mineralization and the ages determined by U-Pb zircon grains of these felsic volcanic rocks range from 170 Ma to 165 Ma indicating Middle Jurassic time. At the 0.1% cut-off grade, 7.5 million tons of resource has been calculated with 0.75 ppm Au, 0.65 wt% Cu, and 0.35 wt% Zn grades. The Say Yayla mineralization consists of massive and semi-massive sulfide minerals and a mineral assemblage represented by predominantly pyrite and chalcopyrite and trace amounts of sphalerite, tennantite and galena. Average base and precious metal grades of the zones occur with >1 wt% Cu are 2 wt% for Cu, 0.7 wt% for Zn, 0.04 wt% for Pb and 1.5 g/t for Au. The sulfur isotope values (delta S-34 VCDT) range from 4.9 parts per thousand to 6.7 parts per thousand for pyrite grains and 4.2 parts per thousand was obtained from the one sphalerite sample. delta O-18 values for the quartz from quartz-rich ore samples were 10.6 parts per thousand and 11.7 parts per thousand delta O-18 (VSMOW)(qtz). delta O-18 (VSMOW)(fluid) values for the ore-forming fluids vary between 0 parts per thousand and 2.4 parts per thousand. Lead isotope compositions of the pyrite minerals were 18.148-18.150 (Pb-206/Pb-204), 15.548-15.550 (Pb-207/Pb-204) and 38.078-38.083 (Pb-208/Pb-204) The geological, geochemical, and isotopic data of the ore and host-rocks reveal that the mineralization is a bimodal-mafic type (Noranda type), which is classified into Cu-Zn group of volcanogenic massive sulfides. Geochemical and geochronological data from the wall rocks further show that mineralization was developed within an ensimatic island arc environment during the Middle Jurassic.
Keywords: Central Pontide; Volcanogenic massive sulfides; Bimodal-mafic type; Say Yayla